2023
DOI: 10.1007/s12178-023-09830-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Involuntary Retirement from Sports Post-Musculoskeletal Injury in Adult Athletes: a Systematic Review

Abstract: Purpose of Review The psychological aspects of musculoskeletal injury are often overlooked in the rehabilitation process. This review examines the effects of musculoskeletal injury on mental health in adult athletes and identifies themes to guide further research. Recent Findings Athletes are at risk for mental health struggles due to high athletic identity and identity foreclosure. Injured athletes have specifically been shown to have higher rates of anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…According to Furie, Park and Wong (2023), approximately 7% of the U.S.A population suffers from depression at one time or another and athletes are no exception. Although the average onset of depression is around age 22, student-athletes may be more susceptible to the disorder, given their unique burden of juggling so many different types of responsibility.…”
Section: Resultsmentioning
confidence: 99%
“…According to Furie, Park and Wong (2023), approximately 7% of the U.S.A population suffers from depression at one time or another and athletes are no exception. Although the average onset of depression is around age 22, student-athletes may be more susceptible to the disorder, given their unique burden of juggling so many different types of responsibility.…”
Section: Resultsmentioning
confidence: 99%
“…These points of association may explain elevated depression rating scores in this population [ 39 ]. Alternately, in considering a population of high-performing athletes dedicated to their athletic identity and role in sport, it is apparent that there is an association between sport-related injury and mental health [ 36 - 38 , 40 , 41 ]. Over the course of 5 academic years, from 2009-2010 to 2013-2014, over 1 million injuries were estimated within the National Collegiate Athletic Association [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative that we consider the biopsychosocial approach to care when addressing musculoskeletal pain. Acute or chronic pain is recognized as a contributing factor to an individual's mental health [36][37][38][39]. Pain post orthopedic intervention can be associated with long-term disability, increased restrictions in work or daily living, and decreased satisfaction overall [39].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 A study by Furie et al. 30 found that injured athletes showed greater rates of anxiety and depression compared with the general population and those who had to involuntarily retire from their sport had increased psychological distress. These data suggest that earlier surgical intervention for injuries such as proximal hamstring ruptures, when properly indicated, may reduce impact on mental health.…”
Section: Discussionmentioning
confidence: 99%